Durable full-shading honeycomb blind fabric and preparation method thereof

By adding the modified black masterbatch and filler modifier to the PET film and processing it with the non-woven fabric, the problem of the existing fully-shaded honeycomb curtain fabric falling off when the temperature and humidity changes, and achieving higher durability and stability.

CN119820875AActive Publication Date: 2025-04-15连云港市汉恒节能窗饰有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510308295.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-15
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

The existing fully-shaded honeycomb curtain fabrics are prone to cause the aluminum coating to fall off when the ambient temperature and humidity change, affecting the product's use efficiency.

Method used

The PET film and non-woven fabric are combined to make a fully-shaded honeycomb curtain fabric. The PET film is added with modified black masterbatch and filler modifier to optimize the product's full-shading, temperature and humidity stability through the coordination and coordination of raw materials.

Benefits of technology

It significantly improves the durability and stability of the product, ensuring that excellent light shading and use efficiency can be maintained under changing temperature and humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of a durable full-shading honeycomb blind fabric, and relates to the technical field of fabrics, and the preparation method comprises the following steps: preparation of a PET film: uniformly and fully mixing 35-40 parts of polyethylene glycol terephthalate, 2-5 parts of polyethylene wax, 2-4 parts of an antioxidant 1010, 4-7 parts of modified black color master batch, 3-5 parts of a filler modifier and 2-3 parts of calcium stearate; the product is fed into a mold to be extruded and subjected to curtain coating to form a film, and a PET film is obtained; the PET film and non-woven fabric are compounded and processed into the full-shading honeycomb blind fabric. According to the durable full-shading honeycomb blind fabric, the PET film is matched with the non-woven fabric to be compounded and processed into the full-shading honeycomb blind fabric, the modified black color master batch and the filler modifier are added in the PET film preparation process, the full-shading performance of the product is optimized through coordination and matching of the raw materials, and meanwhile the temperature-resistant and humidity-resistant stability effects of the product are remarkable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fabrics, and in particular to a durable full-light-shielding honeycomb curtain fabric and a preparation method thereof. Background Art

[0002] There are many types of curtains, including roller blinds, pull blinds and honeycomb blinds. Honeycomb blinds, also known as accordion blinds, have UV protection and heat insulation functions and are deeply loved by the people. Honeycomb blinds generally include a top rod, a bottom rod and honeycomb blind fabric with threading holes. The honeycomb blind fabric is connected to the top rod and the bottom rod through the ropes in the threading holes. The honeycomb blind fabric is generally made of non-woven fabric.

[0003] The existing fully light-shielding honeycomb blind fabric is made of transparent PET film for aluminum plating. The light-shielding property depends on the thickness of the aluminum plating layer. The aluminum plating layer of the product will fall off due to the ambient temperature and humidity, affecting the use efficiency of the product. Based on this, the present invention further improves it. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a durable full-light-shielding honeycomb blind fabric and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a method for preparing a durable full-light-shielding honeycomb curtain fabric, comprising the following steps: Step 1: Preparation of PET film: Mix 35-40 parts of polyethylene terephthalate, 2-5 parts of polyethylene wax, 2-4 parts of antioxidant 1010, 4-7 parts of modified black masterbatch, 3-5 parts of filler modifier, and 2-3 parts of calcium stearate thoroughly; The above product is sent into a mold for extrusion and cast into a film to obtain a PET film; Step 2: Compound the above PET film with non-woven fabric to produce full light-shielding honeycomb curtain fabric.

[0006] Preferably, the temperature of the film casting is 190°C.

[0007] Preferably, the preparation method of the modified black masterbatch is: S1: 4-7 parts of graphene, 2-5 parts of silane coupling agent, 3-7 parts of montmorillonite and 5-8 parts of 5% by mass lanthanum chloride solution are mixed and stirred thoroughly, and after the stirring is completed, the mixture is filtered and dried to obtain modified graphene; 20-30 parts of carbon black and 10-15 parts of modified graphene are added to 55-65 parts of sulfuric acid solution, and ultrasonically dispersed to obtain a dispersion; S2: The dispersion and the modified additive are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified black masterbatch.

[0008] Preferably, the power of the ultrasonic dispersion treatment in S1 is 450-550 W, the ultrasonic time is 35-45 min, the mass fraction of the sulfuric acid solution is 5-8%, and the silane coupling agent is silane coupling agent KH550.

[0009] Preferably, the preparation method of the modified additive is: 2-5 parts of boron nitride and 1-3 parts of nano titanium dioxide are added to 5-8 parts of yttrium nitrate solution, and then 3-5 parts of hydroxyapatite are added, stirred fully, filtered and dried to obtain a modified additive.

[0010] Preferably, the mass fraction of the yttrium nitrate solution is 2-5%.

[0011] Preferably, the preparation method of the filler modifier is: S11: mixing the nano calcium carbonate, sodium alginate solution and urea solution in a weight ratio of 5:4:3 to obtain a modified solution; S12: Silicon carbide whiskers and carbon nanotubes are compounded in a weight ratio of 3:1, and then sintered at 155°C for 1 hour. After the sintering is completed, a composite material is obtained. The composite material is then added to a modified liquid in a weight ratio of 2:5 and stirred. After the stirring is completed, the mixture is filtered and dried to obtain a filler modifier.

[0012] Preferably, the mass fraction of the sodium alginate solution is 2-5%; the mass fraction of the urea solution is 3-6%.

[0013] Preferably, the stirring speed of the stirring treatment is 450-550 r / min, and the stirring time is 1 hour.

[0014] The invention also provides a durable full-light-shielding honeycomb curtain fabric prepared by a method for preparing the durable full-light-shielding honeycomb curtain fabric.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The durable full-light-shielding honeycomb curtain fabric of the present invention is made of a PET film and a non-woven fabric composite processing to form the full-light-shielding honeycomb curtain fabric. The PET film is made by adding a modified black masterbatch and a filler modifier. The full-light-shielding property of the product is optimized through the coordination of the raw materials, and the temperature resistance and humidity resistance of the product are significantly improved. The modified black masterbatch adopts the graphene of the present invention, montmorillonite, and lanthanum chloride solution to obtain the modified graphene. The modified graphene is combined with carbon black through a sulfuric acid solution, and then subjected to a modified additive ball milling improvement treatment. The boron nitride, nano titanium dioxide and other raw materials in the modified additive are blended and coordinated, thereby optimizing the product performance effect. The modified black masterbatch is blended and coordinated with the filler modifier. The performance of the product is further improved through the coordination and synergy between the raw materials. DETAILED DESCRIPTION

[0016] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] A method for preparing a durable full-light-shielding honeycomb curtain fabric of this embodiment comprises the following steps: Step 1: Preparation of PET film: Mix 35-40 parts of polyethylene terephthalate, 2-5 parts of polyethylene wax, 2-4 parts of antioxidant 1010, 4-7 parts of modified black masterbatch, 3-5 parts of filler modifier, and 2-3 parts of calcium stearate thoroughly; The above product is sent into a mold for extrusion and cast into a film to obtain a PET film; Step 2: Compound the above PET film with non-woven fabric to produce full light-shielding honeycomb curtain fabric.

[0018] The temperature of the cast film in this embodiment is 190°C.

[0019] The preparation method of the modified black masterbatch of this embodiment is: S1: 4-7 parts of graphene, 2-5 parts of silane coupling agent, 3-7 parts of montmorillonite and 5-8 parts of 5% by mass lanthanum chloride solution are mixed and stirred thoroughly, and after the stirring is completed, the mixture is filtered and dried to obtain modified graphene; 20-30 parts of carbon black and 10-15 parts of modified graphene are added to 55-65 parts of sulfuric acid solution, and ultrasonically dispersed to obtain a dispersion; S2: The dispersion and the modified additive are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified black masterbatch.

[0020] In S1 of this embodiment, the power of ultrasonic dispersion treatment is 450-550 W, the ultrasonic time is 35-45 min, the mass fraction of sulfuric acid solution is 5-8%, and the silane coupling agent is silane coupling agent KH550.

[0021] The preparation method of the modified additive of this embodiment is: 2-5 parts of boron nitride and 1-3 parts of nano titanium dioxide are added to 5-8 parts of yttrium nitrate solution, and then 3-5 parts of hydroxyapatite are added, stirred fully, filtered and dried to obtain a modified additive.

[0022] The mass fraction of the yttrium nitrate solution in this embodiment is 2-5%.

[0023] The preparation method of the filler modifier of this embodiment is: S11: mixing the nano calcium carbonate, sodium alginate solution and urea solution in a weight ratio of 5:4:3 to obtain a modified solution; S12: Silicon carbide whiskers and carbon nanotubes are compounded in a weight ratio of 3:1, and then sintered at 155°C for 1 hour. After the sintering is completed, a composite material is obtained. The composite material is then added to a modified liquid in a weight ratio of 2:5 and stirred. After the stirring is completed, the mixture is filtered and dried to obtain a filler modifier.

[0024] The mass fraction of the sodium alginate solution in this embodiment is 2-5%; the mass fraction of the urea solution is 3-6%.

[0025] The stirring speed of the stirring treatment in this embodiment is 450-550 r / min, and the stirring is for 1 hour.

[0026] The durable full-light-blocking honeycomb shade fabric is prepared by a method for preparing a durable full-light-blocking honeycomb shade fabric in this embodiment.

[0027] Embodiment 1: A method for preparing a durable full-light-shielding honeycomb curtain fabric of this embodiment comprises the following steps: Step 1: Preparation of PET film: Mix 35 parts of polyethylene terephthalate, 2 parts of polyethylene wax, 2 parts of antioxidant 1010, 4 parts of modified black masterbatch, 3 parts of filler modifier and 2 parts of calcium stearate thoroughly; The above product is sent into a mold for extrusion and cast into a film to obtain a PET film; Step 2: Compound the above PET film with non-woven fabric to produce full light-shielding honeycomb curtain fabric.

[0028] The temperature of the cast film in this embodiment is 190°C.

[0029] The preparation method of the modified black masterbatch of this embodiment is: S1: 4 parts of graphene, 2 parts of silane coupling agent, 3 parts of montmorillonite and 5 parts of 5% by mass lanthanum chloride solution are mixed and stirred thoroughly, and after the stirring is completed, the mixture is filtered and dried to obtain modified graphene; 20 parts of carbon black and 10 parts of modified graphene are added to 55 parts of sulfuric acid solution and subjected to ultrasonic dispersion treatment to obtain a dispersion; S2: The dispersion and the modified additive are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified black masterbatch.

[0030] In S1 of this embodiment, the power of ultrasonic dispersion treatment is 450 W, the ultrasonic time is 35 min, the mass fraction of sulfuric acid solution is 5%, and the silane coupling agent is silane coupling agent KH550.

[0031] The preparation method of the modified additive of this embodiment is: 2 parts of boron nitride and 1 part of nano titanium dioxide are added to 5 parts of yttrium nitrate solution, and then 3 parts of hydroxyapatite are added, stirred sufficiently, filtered and dried to obtain a modified additive.

[0032] The mass fraction of the yttrium nitrate solution in this embodiment is 2%.

[0033] The preparation method of the filler modifier of this embodiment is: S11: mixing the nano calcium carbonate, sodium alginate solution and urea solution in a weight ratio of 5:4:3 to obtain a modified solution; S12: Silicon carbide whiskers and carbon nanotubes are compounded in a weight ratio of 3:1, and then sintered at 155°C for 1 hour. After the sintering is completed, a composite material is obtained. The composite material is then added to a modified liquid in a weight ratio of 2:5 and stirred. After the stirring is completed, the mixture is filtered and dried to obtain a filler modifier.

[0034] The mass fraction of the sodium alginate solution in this embodiment is 2%; the mass fraction of the urea solution is 3%.

[0035] The stirring speed of the stirring process in this embodiment is 450 r / min, and the stirring is performed for 1 hour.

[0036] The durable full-light-blocking honeycomb shade fabric is prepared by a method for preparing a durable full-light-blocking honeycomb shade fabric in this embodiment.

[0037] Embodiment 2: A method for preparing a durable full-light-shielding honeycomb curtain fabric of this embodiment comprises the following steps: Step 1: Preparation of PET film: Mix 40 parts of polyethylene terephthalate, 5 parts of polyethylene wax, 4 parts of antioxidant 1010, 7 parts of modified black masterbatch, 5 parts of filler modifier and 3 parts of calcium stearate thoroughly; The above product is sent into a mold for extrusion and cast into a film to obtain a PET film; Step 2: Compound the above PET film with non-woven fabric to produce full light-shielding honeycomb curtain fabric.

[0038] The temperature of the cast film in this embodiment is 190°C.

[0039] The preparation method of the modified black masterbatch of this embodiment is: S1: 7 parts of graphene, 5 parts of silane coupling agent, 7 parts of montmorillonite and 8 parts of 5% by mass lanthanum chloride solution are mixed and stirred thoroughly, and after the stirring is completed, the mixture is filtered and dried to obtain modified graphene; 30 parts of carbon black and 15 parts of modified graphene are added to 65 parts of sulfuric acid solution and subjected to ultrasonic dispersion treatment to obtain a dispersion; S2: The dispersion and the modified additive are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified black masterbatch.

[0040] In S1 of this embodiment, the power of ultrasonic dispersion treatment is 550 W, the ultrasonic time is 45 min, the mass fraction of sulfuric acid solution is 8%, and the silane coupling agent is silane coupling agent KH550.

[0041] The preparation method of the modified additive of this embodiment is: 5 parts of boron nitride and 3 parts of nano titanium dioxide are added to 8 parts of yttrium nitrate solution, and then 5 parts of hydroxyapatite are added, stirred sufficiently, filtered and dried to obtain a modified additive.

[0042] The mass fraction of the yttrium nitrate solution in this embodiment is 5%.

[0043] The preparation method of the filler modifier of this embodiment is: S11: mixing the nano calcium carbonate, sodium alginate solution and urea solution in a weight ratio of 5:4:3 to obtain a modified solution; S12: Silicon carbide whiskers and carbon nanotubes are compounded in a weight ratio of 3:1, and then sintered at 155°C for 1 hour. After the sintering is completed, a composite material is obtained. The composite material is then added to a modified liquid in a weight ratio of 2:5 and stirred. After the stirring is completed, the mixture is filtered and dried to obtain a filler modifier.

[0044] The mass fraction of the sodium alginate solution in this embodiment is 5%; the mass fraction of the urea solution is 6%.

[0045] The stirring speed of the stirring process in this embodiment is 550 r / min, and the stirring is performed for 1 hour.

[0046] The durable full-light-blocking honeycomb shade fabric is prepared by a method for preparing a durable full-light-blocking honeycomb shade fabric in this embodiment.

[0047] Embodiment 3: A method for preparing a durable full-light-shielding honeycomb curtain fabric of this embodiment comprises the following steps: Step 1: Preparation of PET film: Mix 37.5 parts of polyethylene terephthalate, 3.5 parts of polyethylene wax, 3 parts of antioxidant 1010, 5.5 parts of modified black masterbatch, 4 parts of filler modifier and 2.5 parts of calcium stearate thoroughly; The above product is sent into a mold for extrusion and cast into a film to obtain a PET film; Step 2: Compound the above PET film with non-woven fabric to produce full light-shielding honeycomb curtain fabric.

[0048] The temperature of the cast film in this embodiment is 190°C.

[0049] The preparation method of the modified black masterbatch of this embodiment is: S1: 5.5 parts of graphene, 3.5 parts of silane coupling agent, 5 parts of montmorillonite and 6.5 parts of 5% by mass lanthanum chloride solution are mixed and stirred thoroughly, and after the stirring is completed, the mixture is filtered and dried to obtain modified graphene; 25 parts of carbon black and 12.5 parts of modified graphene are added to 60 parts of sulfuric acid solution and subjected to ultrasonic dispersion treatment to obtain a dispersion; S2: The dispersion and the modified additive are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified black masterbatch.

[0050] In S1 of this embodiment, the power of ultrasonic dispersion treatment is 500 W, and the ultrasonic time is 40 min; the mass fraction of sulfuric acid solution is 6.5%; and the silane coupling agent is silane coupling agent KH550.

[0051] The preparation method of the modified additive of this embodiment is: 3.5 parts of boron nitride and 2 parts of nano titanium dioxide are added to 6.5 parts of yttrium nitrate solution, and then 4 parts of hydroxyapatite are added, stirred sufficiently, filtered and dried to obtain a modified additive.

[0052] The mass fraction of the yttrium nitrate solution in this embodiment is 3.5%.

[0053] The preparation method of the filler modifier of this embodiment is: S11: mixing the nano calcium carbonate, sodium alginate solution and urea solution in a weight ratio of 5:4:3 to obtain a modified solution; S12: Silicon carbide whiskers and carbon nanotubes are compounded in a weight ratio of 3:1, and then sintered at 155°C for 1 hour. After the sintering is completed, a composite material is obtained. The composite material is then added to a modified liquid in a weight ratio of 2:5 and stirred. After the stirring is completed, the mixture is filtered and dried to obtain a filler modifier.

[0054] The mass fraction of the sodium alginate solution in this embodiment is 3.5%; the mass fraction of the urea solution is 4.5%.

[0055] The stirring speed of the stirring process in this embodiment is 500 r / min, and the stirring is performed for 1 hour.

[0056] The durable full-light-blocking honeycomb shade fabric is prepared by a method for preparing a durable full-light-blocking honeycomb shade fabric in this embodiment.

[0057] Embodiment 4: A method for preparing a durable full-light-shielding honeycomb curtain fabric of this embodiment comprises the following steps: Step 1: Preparation of PET film: Mix 36 parts of polyethylene terephthalate, 3 parts of polyethylene wax, 3 parts of antioxidant 1010, 5 parts of modified black masterbatch, 4 parts of filler modifier and 2 parts of calcium stearate thoroughly; The above product is sent into a mold for extrusion and cast into a film to obtain a PET film; Step 2: Compound the above PET film with non-woven fabric to produce full light-shielding honeycomb curtain fabric.

[0058] The temperature of the cast film in this embodiment is 190°C.

[0059] The preparation method of the modified black masterbatch of this embodiment is: S1: 5 parts of graphene, 3 parts of silane coupling agent, 4 parts of montmorillonite and 6 parts of 5% by mass lanthanum chloride solution are mixed and stirred thoroughly, and after the stirring is completed, the mixture is filtered and dried to obtain modified graphene; 28 parts of carbon black and 14 parts of modified graphene are added to 62 parts of sulfuric acid solution and subjected to ultrasonic dispersion treatment to obtain a dispersion; S2: The dispersion and the modified additive are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified black masterbatch.

[0060] In S1 of this embodiment, the power of ultrasonic dispersion treatment is 540 W, the ultrasonic time is 42 min, the mass fraction of sulfuric acid solution is 7%, and the silane coupling agent is silane coupling agent KH550.

[0061] The preparation method of the modified additive of this embodiment is: 4 parts of boron nitride and 2 parts of nano titanium dioxide are added to 6 parts of yttrium nitrate solution, and then 4 parts of hydroxyapatite are added, stirred sufficiently, filtered and dried to obtain a modified additive.

[0062] The mass fraction of the yttrium nitrate solution in this embodiment is 4%.

[0063] The preparation method of the filler modifier of this embodiment is: S11: mixing the nano calcium carbonate, sodium alginate solution and urea solution in a weight ratio of 5:4:3 to obtain a modified solution; S12: Silicon carbide whiskers and carbon nanotubes are compounded in a weight ratio of 3:1, and then sintered at 155°C for 1 hour. After the sintering is completed, a composite material is obtained. The composite material is then added to a modified liquid in a weight ratio of 2:5 and stirred. After the stirring is completed, the mixture is filtered and dried to obtain a filler modifier.

[0064] The mass fraction of the sodium alginate solution in this embodiment is 4%; the mass fraction of the urea solution is 5%.

[0065] The stirring speed of the stirring process in this embodiment is 540 r / min, and the stirring is performed for 1 hour.

[0066] The durable full-light-blocking honeycomb shade fabric is prepared by a method for preparing a durable full-light-blocking honeycomb shade fabric in this embodiment.

[0067] Comparative Example 1. The difference from Example 3 is that the modified black masterbatch is replaced by carbon black.

[0068] Comparative Example 2. The difference from Example 3 is that no modifying additive is added in the preparation of the modified black masterbatch.

[0069] Comparative Example 3. The difference from Example 3 is that boron nitride and nano titanium dioxide are not added in the preparation of the modified additive.

[0070] Comparative Example 4. The difference from Example 3 is that no filler modifier is added.

[0071] Comparative Example 5. The difference from Example 3 is that no modifying liquid is added in the preparation of the filler modifier.

[0072] The product performance tests of Examples 1-4 and Comparative Examples 1-5 were conducted by placing the products under 5% humidity for 24 hours and at 75°C for 12 hours to test the humidity resistance and temperature stability of the products. The test results are as follows:

[0073] It can be seen from Comparative Examples 1-5 and Example 3 that the product of Example 3 has excellent shading power and significant durability and stability. The modified black masterbatch in the product is replaced by carbon black, no filler modifier is added, and no modifying additive is added in the preparation of the modified black masterbatch, no boron nitride and nano-titanium dioxide are added in the preparation of the modified additive, and no modifying liquid is added in the preparation of the filler modifier. The performance of the product tends to deteriorate. Only the product raw material obtained by the method of the present invention has the most significant product performance effect.

[0074] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0075] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a durable full-light-shielding honeycomb curtain fabric, characterized in that: The following steps are involved: Step 1: Preparation of PET film: Mix 35-40 parts of polyethylene terephthalate, 2-5 parts of polyethylene wax, 2-4 parts of antioxidant 1010, 4-7 parts of modified black masterbatch, 3-5 parts of filler modifier, and 2-3 parts of calcium stearate thoroughly; The above product is sent into a mold for extrusion and cast into a film to obtain a PET film; Step 2: Compounding the PET film and non-woven fabric to produce a fully light-shielding honeycomb curtain fabric; The preparation method of the modified black masterbatch is: S1: 4-7 parts of graphene, 2-5 parts of silane coupling agent, 3-7 parts of montmorillonite and 5-8 parts of 5% by mass lanthanum chloride solution are mixed and stirred thoroughly, and after the stirring is completed, the mixture is filtered and dried to obtain modified graphene; 20-30 parts of carbon black and 10-15 parts of modified graphene are added to 55-65 parts of sulfuric acid solution, and ultrasonically dispersed to obtain a dispersion; S2: The dispersion and the modified additive are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain a modified black masterbatch.

2. A method for preparing a durable full-light-shielding honeycomb curtain fabric according to claim 1, characterized in that: The temperature of the film casting was 190°C.

3. The method for preparing a durable full-light-shielding honeycomb curtain fabric according to claim 1, characterized in that: The power of the ultrasonic dispersion treatment in S1 is 450-550 W, and the ultrasonic time is 35-45 min; the mass fraction of the sulfuric acid solution is 5-8%; and the silane coupling agent is silane coupling agent KH550.

4. The method for preparing a durable full-light-shielding honeycomb curtain fabric according to claim 3, characterized in that: The preparation method of the modified additive is: 2-5 parts of boron nitride and 1-3 parts of nano titanium dioxide are added to 5-8 parts of yttrium nitrate solution, and then 3-5 parts of hydroxyapatite are added, stirred fully, filtered and dried to obtain a modified additive.

5. A method for preparing a durable full-light-shielding honeycomb curtain fabric according to claim 4, characterized in that: The mass fraction of the yttrium nitrate solution is 2-5%.

6. The method for preparing a durable full-light-shielding honeycomb curtain fabric according to claim 1, characterized in that: The preparation method of the filler modifier is: S11: mixing the nano calcium carbonate, sodium alginate solution and urea solution in a weight ratio of 5:4:3 to obtain a modified solution; S12: Silicon carbide whiskers and carbon nanotubes are compounded in a weight ratio of 3:1, and then sintered at 155°C for 1 hour. After the sintering is completed, a composite material is obtained. The composite material is then added to a modified liquid in a weight ratio of 2:5 and stirred. After the stirring is completed, the mixture is filtered and dried to obtain a filler modifier.

7. A method for preparing a durable full-light-shielding honeycomb curtain fabric according to claim 6, characterized in that: The mass fraction of the sodium alginate solution is 2-5%; the mass fraction of the urea solution is 3-6%.

8. The method for preparing a durable full-light-shielding honeycomb curtain fabric according to claim 6, characterized in that: The stirring speed of the stirring treatment is 450-550 r / min, and the stirring is performed for 1 hour.

9. A durable full-light-blocking honeycomb shade fabric prepared by the method for preparing a durable full-light-blocking honeycomb shade fabric according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Full-light-shading polyolefin greenhouse curtain

    CN104742451A

  • Preparation process of plastic master batch

    CN111673941A

  • Environment-friendly bio-based high-shading flame-retardant composite material and preparation method thereof

    CN111890742A

  • Black BOPET film and preparation method thereof

    CN115746511A

  • Ultraviolet-proof automobile heat insulation film and preparation method thereof

    CN117567951A